Peningkatan Hasil Bisnis Mochi Mitra (Mochi 3R) Dengan Melakukan Sub-Branding - Utomo, Alvin; Bella, Annastasia; Narjosusilo, David Ivan; Loekmanhadi, Gracesella; Changgrawinata, Julius; Bustamin, Stephanie; Kuntjoro*, Antonius Puspo (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
Community Development is one of the best program of Prasetiya Mulya University in collaboration with various small businesses in remote areas of Cianjur and Cipanas. We had the opportunity to help Ms. Wiwi's mochi business in Cianjur. Mochi production by the community, especially Taman Jaya Dua Village, Gadog Village, Pacet District, Cianjur Regency, has high potential to be developed both in terms of quantity and quality. Many processes must be passed as the time goes by to help develop partners' mochi businesses, including increasing standardization and sub-branding of mochi styles, compiling production SOPs, using safe preservatives, making online marketing media, adding competent workforce, and monitoring business financial performance independent. Our results are very satisfying. Ms. Wiwi as the business owner is also very happy and open with the input we provide. The results we get from Community Service activities are very satisfying as well. The income earned by Ms. Wiwi has also improved in line with the development of Mochi Gaya.